Extranodal Rosai-Dorfman Disease Involving the Left Atrium: Cardiac MRI, CT, and PET Scan Findings - Vistasp J. Daruwalla; Keyur Parekh; Hassan Tahir; Jeremy D. Collins; James Carr (Case Reports in Radiology)
Rosai-Dorfman disease (RDD) is a rare entity that usually involves the lymph nodes but extranodal involvements have been seen in numerous cases, although RDD with cardiovascular involvement is extremely rare. We describe a case of a young male who presented with intermittent palpitations and was found to have a left atrium mass. Our case not only emphasizes the rarity of the above lesion but also highlights the importance of modern-day imaging like computed tomography, Cardiac Magnetic Resonance Imaging (CMRI), and PET scan in characterizing such nonspecific lesions and directing appropriate line of treatment. RDD should be considered as one of the differentials even for isolated cardiac lesions.